Effects of flaked and roasted sorghum grain on finishing swine performance - Allee, G.L.; Hines, Robert H. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
The value of feeding flaked or roasted sorghum grain to finishing swine (95 to 210 lbs.) was investigated using 54 barrows and gilts. Rate and efficiency of gain for each treatment group were similar. Data from this station indicate that processing methods like flaking or roasting sorghum grain do not improve the performance of finishing swine enough to offset the increased cost of processing.
Swine Industry Day 1972 is known as Swine Day 1972
Keywords: Swine; Flaked and roasted sorghum grain; Finishing pigs; Rate of gain